PEMENUHAN KEBUTUHAN OKSIGENASI DENGAN PEMBERIAN POSISI HEAD UP 30˚ PADA PASIEN STROKE - abd Hady junaidi; Abdul Kadir Akhmad; Suci Faradilah; Baharuddin K; Rauf Harmiady (Media Keperawatan:Politeknik Kesehatan Makassar, 2023)
Stroke as cerebrovascular damage, is a loss of brain function caused by cessation or reduced blood supply to an area of the brain, resulting in local or global neurological dysfunction. Substandard blood flow in stroke patients can lead to hemodynamic abnormalities, where hemodynamic conditions affect the distribution of oxygen throughout the body, affect heart function and reduce oxygen saturation so that stroke is an emergency case and requires fast and appropriate help. Purpose: of this study was to determine how to fulfill the need for oxygenation by giving a 30˚ head up position in stroke patients. Method: used is a literature study or literature review using articles/journals in the form of fulfilling oxygen needs by giving a 30˚ head up position in stroke patients. Results: showed that there was a significant increase in oxygen saturation levels after the 30˚ head up position in stroke patients. Conclusion :of this study is that one of the interventions that can be carried out in fulfilling oxygenation in stroke patients is giving a 30 head up position with a head elevation or 30˚ head up position that can facilitate increased cerebral blood flow and maximize cerebral tissue oxygenation